Associação entre consumo materno de alimentos ultraprocessados, práticas alimentares e estado nutricional em lactentes menores de 6 meses - Sousa, Juliana Morais de (2023)
Despite the negative impact of consumption of ultra-processed foods (UPF) on health already being widely reported in the literature, there is still there little evidence on the consequences of maternal UPF consumption on the health of their offspring during lactation. Given this gap, the objective of this study was to evaluate the association between maternal UPF consumption, feeding practices and malnutrition of their infants. This is a cross-sectional study carried out with 111 mother-child pairs up to 150 days postpartum, assisted in the growth and development monitoring program of the primary health care in Natal-RN. Feeding practices related to breastfeeding were evaluated using six indicators. Malnutrition was assessed by weight-for-age z-score, length-for-age and BMI-for-age, according to the WHO growth charts. Maternal consumption was obtained using two 24-hour recalls and foods were categorized according to the NOVA classification. The binomial was grouped according to the highest quartile of energy participation of maternal UPF consumption (<Percentile 75, named Q1-3 and ≥ Percentile 75, named Q4). Binary logistic regression models adjusted for the variables income, maternal education, exclusive breastfeeding (EBF), birth weight and length, were used to estimate the association between maternal UPF consumption, inappropriate feeding practices and malnutrition (wasting or overweight and stunting) according to by weight-for-age z-score, length-for-age and BMI-for-age. The women were 28 years old, 36% had not completed high school, most were under on the poverty line (66.7%, n=74) and the participation of UPF in the maternal diet was 26.24% (0-44 CI 95%). The infants had an average of 61 days old, 72.8% were on EBF at the time of the interview and only 58.6% had received colostrum milk, exclusively. One third of the infants were overweight and 11.7% were stunting, with a significant association being found between the highest quartile of UPF participation in the maternal diet and the chance of presenting some malnutrition in the infant (wasting or overweight) (OR 3.38 95%CI: 1.29 - 8.83) and stunting (OR 3.89; 95%CI 1.04 – 14.58). However, there was no association with feeding practices. The findings demonstrate that UPF consumption during lactation was associated with malnutrition in breastfed infants of study. These results also highlight the need for greater attention to nutritional assistance during lactation, since the impacts on growth during lactation and early childhood can induce long-term effects, including failures in growth and development of NCD in adulthood